Symphytum officinale augments osteogenesis in human bone marrow-derived mesenchymal stem cells in vitro as they differentiate into osteoblasts. (10th February 2020) - Dey, D; Jingar, P; Agrawal, S; Shrivastava, V; Bhattacharya, A; Manhas, J; Garg, B; Ansari, M.T.; Mridha, A.R.; Sreenivas, V; Khurana, A; Sen, S
Abstract: Ethnopharmacological relevance: Mesenchymal stem cells (MSCs) are multipotent stem cells possessing regenerative potential. Symphytum officinale (SO) is a medicinal plant and in homoeopathic literature, believed to accelerate bone healing. Aim of the study: This study aimed to determine if homoeopathic doses of SO could augment osteogenesis in MSCs as they differentiate into osteoblasts in vitro . Materials and methods: Bone marrow samples were obtained from patients who underwent bone grafting procedures (n = 15). MSCs were isolated, expanded and characterized by flow cytometry (CD90, CD105). Cytotoxicity of SO was evaluated by MTT assay. Osteogenic differentiation was induced in MSCs with β-glycerophosphate, ascorbic acid and dexamethasone over 2 weeks. Different homoeopathic doses of SO (MT, 3C, 6C, 12C and 30C) were added to the basic differentiation medium (BDM) and efficiency of MSCs differentiating into osteoblasts were measured by evaluating expression of Osteocalcin using flow cytometry, and alkaline phosphatase activity using ELISA. Gene expression analyses for osteoblast markers (Runx-2, Osteopontin and Osteocalcin) were evaluated in differentiated osteoblasts using qPCR. Results: Flow cytometry (CD90, CD105) detected MSCs isolated from bone marrow (93–98%). MTT assay showed that the selected doses of SO did not induce any cytotoxicity in MSCs (24 hours). The efficiency of osteogenic differentiation (2 weeks) for different doses of Symphytum officinale was determined by flow cytometry (n = 10) for osteoblast marker, Osteocalcin, and most doses of Symphytum officinale enhanced osteogenesis. Interestingly, gene expression analysis for Runx-2 (n = 10), Osteopontin (n = 10), Osteocalcin (n = 10) and alkaline phosphatase activity (n = 8) also showed increased osteogenesis with the addition of Symphytum officinale to BDM, specially mother tincture. Conclusions: Our findings suggest that homoeopathic dose (specially mother tincture) of Symphytum officinale has the potential to enhance osteogenesis. Graphical abstract: Image 1